Ultrabroadband High Coupling Efficiency Fiber-to-Waveguide Coupler Using Si $_{3}$ N $_{4}$ /SiO $_{2}$ Waveguides on Silicon - Tiecheng Zhu; Yiwen Hu; Pradip Gatkine; Sylvain Veilleux; Joss Bland-Hawthorn; Mario Dagenais (IEEE Photonics Journal)
An easy-to-fabricate but very efficient fiber-to-waveguide coupler is theoretically analyzed and experimentally demonstrated. In this design, light from a single-mode fiber can be butt coupled into a single-mode high-index-contrast Si $_{3}$ N $_{4}$ /SiO $_{2}$ waveguide with a measured coupling efficiency of 96% at the wavelength of 1550 nm and $>$ 90% in the spectral range from 1450 to 1650 nm. Large horizontal and vertical alignment tolerances of 3.8 $μ \text{m}$ and 3.6 $μ \text{m}$ , respectively, are obtained between the fiber and the waveguide coupler. All these experimental results agree well with simulations. The waveguide coupler also features ease of end-facet cleaving and can be used in ultrabroadband high coupling efficiency applications.